2012
DOI: 10.1016/j.canlet.2012.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Biomodulatory approaches to photodynamic therapy for solid tumors

Abstract: Photodynamic Therapy (PDT) uses a photosensitizing drug in combination with visible light to kill cancer cells. PDT has an advantage over surgery or ionizing radiation because PDT can eliminate tumors without causing fibrosis or scarring. Disadvantages include the dual need for drug and light, and a generally lower efficacy for PDT versus surgery. This minireview describes basic principles of PDT, photosensitizers available, and aspects of tumor biology that may provide further opportunities for treatment opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
156
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(159 citation statements)
references
References 82 publications
(100 reference statements)
3
156
0
Order By: Relevance
“…The nonfluorescent PS precursor 5-aminolevulinic acid (5-ALA, trade name Levulan®) enhances the intrinsic production of protoporphyrin IX (PPIX) in mitochondria, which is activated by light illumination (~ 635 nm) following accumulation at the treatment site leading to the effective generation of reactive oxygen species within treated cells and triggering cell death [17,68,69]. The clinical use of topically applied 5-ALA for PDT was first introduced in 1990 [70] and followed by a wide range of clinical and preclinical studies for the PDT treatment of bladder cancer [71][72][73], chronic polyarthritis [74], malignant glioma [75], nonmelanoma skin cancers such as actinic keratosis (in combination with fluorescence dosimetry) [69,76], Barret's oesophagus and even multidrug resistant leukemia, the latter without much success [77]. In 2013 Bader et al reported a clinical trial using hexaminolevulinate (HAL), a 5-ALA derivative, for the PDT of bladder cancer in humans.…”
Section: Progress In Photosensitizer (Ps) Developmentmentioning
confidence: 99%
See 4 more Smart Citations
“…The nonfluorescent PS precursor 5-aminolevulinic acid (5-ALA, trade name Levulan®) enhances the intrinsic production of protoporphyrin IX (PPIX) in mitochondria, which is activated by light illumination (~ 635 nm) following accumulation at the treatment site leading to the effective generation of reactive oxygen species within treated cells and triggering cell death [17,68,69]. The clinical use of topically applied 5-ALA for PDT was first introduced in 1990 [70] and followed by a wide range of clinical and preclinical studies for the PDT treatment of bladder cancer [71][72][73], chronic polyarthritis [74], malignant glioma [75], nonmelanoma skin cancers such as actinic keratosis (in combination with fluorescence dosimetry) [69,76], Barret's oesophagus and even multidrug resistant leukemia, the latter without much success [77]. In 2013 Bader et al reported a clinical trial using hexaminolevulinate (HAL), a 5-ALA derivative, for the PDT of bladder cancer in humans.…”
Section: Progress In Photosensitizer (Ps) Developmentmentioning
confidence: 99%
“…chlorins, bacteriochlorins and phthalocyanines) were developed. Third generation PSs were designed to improve selective tumour targeting and drug accumulation by conjugating common PSs to carriers such as cholesterol, antibodies, and liposomes and therefore reduce unwanted damage to healthy tissues [5,42,69,78]. The section on targeted PDT below (4.7) will cover these developments in more detail.…”
Section: Progress In Photosensitizer (Ps) Developmentmentioning
confidence: 99%
See 3 more Smart Citations